Analysis of Problems Militating Against Effectiveness of Regulatory Agencies of Tertiary Institutions in Nigeria - Ukozor, Conrad Ugochukwu; Peter, Thank God; Ogunode, Niyi Jacob (Researchparks Publishing, 2023)
This paper examined the problems militating against effectiveness of regulatory agencies of tertiary institutions in Nigeria. Quantitative and qualitative data were used to provide empirical support to the various points raised in the paper. The paper concluded that inadequate funding, shortage of staff, inadequate supervisory materials, ineffective capacity building programme, insecurity, corruption, strike actions, limited offices, inadequate transportation facilities and opposition from labor unions are the problems militating against effectiveness of tertiary institutions regulatory agencies in Nigeria. To address these problems, the paper recommended that the government should increase the funding of the regulatory agencies in Nigeria, direct them to employ more staff, provide them with all supervisory materials and ensure effective capacity building problem for the staff. etc.